1998
DOI: 10.1021/bi9803426
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Conserved First 18 N-Terminal Amino Acid Residues in Rat Liver Carnitine Palmitoyltransferase I Abolishes Malonyl-CoA Sensitivity and Binding

Abstract: To assess the role of the 130 N-terminal amino acid residues of rat liver carnitine palmitoyltransferase I (L-CPTI) on malonyl-CoA sensitivity and binding, we constructed a series of mutants with deletions of the 18, 35, 52, 73, 83, or 129 most N-terminal amino acid residues. The deletion mutants were expressed in the yeast Pichia pastoris. We determined the effects of these mutations on L-CPTI activity, malonyl-CoA sensitivity, and binding in isolated mitochondria prepared from the yeast strains expressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…As the catalytic site is thought to reside within the Cterminal domain of the enzyme, and as malonyl-CoA and longchain acyl-CoA binding to the protein appear to mutually interfere at a common site or close-set sites [41], it was suggested that N-to-C interdomain interactions are crucial for the maintenance of the C-domain in a conformation that is optimal for expression of catalytic activity and malonyl-CoA sensitivity. These conclusions have now been confirmed through the expression of mutants of the protein having N-terminal truncations or specific amino acid substitutions [42][43][44]. In particular, the importance of Glu$ and His& for the expression of malonyl-CoA sensitivity has been demonstrated [43,44].…”
Section: Malonyl-coa Action On Cptomentioning
confidence: 78%
“…As the catalytic site is thought to reside within the Cterminal domain of the enzyme, and as malonyl-CoA and longchain acyl-CoA binding to the protein appear to mutually interfere at a common site or close-set sites [41], it was suggested that N-to-C interdomain interactions are crucial for the maintenance of the C-domain in a conformation that is optimal for expression of catalytic activity and malonyl-CoA sensitivity. These conclusions have now been confirmed through the expression of mutants of the protein having N-terminal truncations or specific amino acid substitutions [42][43][44]. In particular, the importance of Glu$ and His& for the expression of malonyl-CoA sensitivity has been demonstrated [43,44].…”
Section: Malonyl-coa Action On Cptomentioning
confidence: 78%
“…P. pastoris was chosen as an expression system for L-CPTI and the mutants, because it does not have endogenous CPT activity (6,(12)(13)(14)(15)(16). The P. pastoris expression plasmids expressed L-CPTI under control of the P. pastoris glyceraldehyde-3-phosphate dehydrogenase gene promoter (12,22).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by using this system, we have shown that CPTI and CPTII are active distinct enzymes and that L-CPTI and M-CPTI are distinct malonyl-CoA-sensitive CPTs that are reversibly inactivated by detergents. Recent site-directed mutagenesis studies from our laboratory have demonstrated that glutamic acid 3 and histidine 5 in L-CPTI are necessary for malonyl-CoA inhibition and high affinity binding but not for catalysis (15,16). For M-CPTI, our mutagenesis studies demonstrate that in addition to Glu-3 and His-5, Val-19, Leu-23, and Ser-24 are necessary for malonyl-CoA inhibition and high affinity binding, in agreement with the differences in malonyl-CoA sensitivity observed between M-CPTI and L-CPTI (17).…”
mentioning
confidence: 99%
“…The Nterminal domain, which contains both TM1 and TM2 domains, was shown to be responsible for mitochondrial import and for maintenance of a folded enzymatically active and malonyl-CoAsensitive conformation [19]. Moreover, the nature of the cytosolic N-C (N-and C-terminal domain) interactions determine the degree of malonyl-CoA sensitivity of the liver isoform [2,21].…”
Section: Introductionmentioning
confidence: 99%